Pericyclic Cascade toward Isochromenes: Application to the Synthesis of Alkaloid Benzosimuline - Riveira, Martín Jorge (2016)
The synthesis of biologically active alkaloid benzosimuline, isolated from the shrub Zanthoxylum simulans, is reported. Key transformation involves an oxa-6π electrocyclic ring-opening/hetero-Diels-Alder pericyclic cascade. Although the last aromatization step proved to be cumbersome, this work unfolds a unique route to access interesting molecules from simple precursors.